DAKWAH ISLAM SEBAGAI WAHANA PENDIDIKAN MODERASI BAGI MUSLIMAH: Islamic Da'wah As A Vehicle For Moderation Education For Muslimah - Nadiah Yusfi Nabilah; Devy Habibi Muhammad (TA'LIMUNA: Jurnal Pendidikan Islam, 2026)
This article examines Islamic da'wah as an educational tool to promote religious moderation among Muslim women. This article employs a literature review research method. Data was collected using documentation techniques. The data was then analyzed using content analysis. The results of the study reveal three forms of religious moderation among Muslim women in Indonesia. First, religious moderation in creed is manifested by adhering to a sound and unified concept of tawhid. Second, religious moderation in ethics is manifested by fostering harmonious social relationships with fellow human beings. Third, religious moderation in culture is manifested through mutual cooperation among members of Indonesia’s multicultural society.  Artikel ini menelaah dakwah Islam sebagai sarana pendidikan untuk mendorong moderasi beragama di kalangan wanita Muslim. Artikel ini menggunakan metode penelitian studi pustaka. Pengumpulan data dengan teknik dokumentasi. Lalu data dianalisis dengan teknik analisis isi. Hasil penelitian menunjukkan tiga bentuk moderasi beragama bagi Muslimah di Indonesia. Pertama, moderasi beragama dalam akidah diwujudkan dengan mengikuti tauhid yang lurus dan tidak bercerai-berai. Kedua, moderasi beragama dalam akhlak diwujudkan dengan menjalin hubungan sosial yang harmonis dengan sesama manusia. Ketiga, moderasi beragama dalam budaya diwujudkan dengan gerakan gotong royong dalam anggota masyarakat Indonesia yang multikultural.    Kata Kunci : Dakwah Islam; Moderasi Beragama; Muslimah.